THE EFFECT OF SOCIAL MEDIA MARKETING ON THE PURCHASE DECISION OF KOOKA COFFEE PRODUCTS USING BRAND IMAGE AS A MEDIATION VARIABLE - Rishona Hanael Tauran; Dwi Retno Andriani; Agustina Shinta Hartati Wahyuningtyas; Riyanti Isaskar (Socio-Economics/Agribusiness Department, 2022)
This research is motivated by the increasingly high competition between coffee shops which encourages coffee shops to have more creative and innovative strategies. Some of the existing coffee shops have done social media marketing, which makes delivering product information easier, has affordable prices and has a broader market reach. Information that is shared through social media needs to be adequately packaged and attractively because it can increase customer satisfaction and brand image, which plays an essential role in the success of coffee shops during increasingly high competition. Kooka Coffee is the pioneer coffee shop that collaborates with clothing convection, producing advantages that other coffee shops do not. Kooka Coffee uses Instagram to share various marketing information that it hopes will increase its brand image in the minds of consumers and can have an impact in improving purchasing decisions. The goal of this study is to identify the most influential indicators on Kooka Coffee consumers' social media marketing, brand image, and purchasing decisions, as well as the effect of social media marketing on Instagram against brand image and purchasing decisions, and the influence of social media marketing on Kooka Coffee Malang consumers' purchasing decisions mediated by brand image.. This study used 100 respondents who were determined by the method purposive sampling. Analysis path used to calculate the effect between variables social media marketing with purchasing decision variables directly and indirectly through brand image. The analysis results show that social media marketing has a positive and significant effect on brand image, social media marketing positive and insignificant effect on purchasing decisions, brand image has a positive and significant impact on purchasing decisions, and brand image mediates with influence of social media marketing on buying decisions.